New species of Chnoodes Chevrolat (Coleoptera: Coccinellidae) from French Guiana - Krüger, Thaysa C.; Churata, Julissa S.; Castro-Guedes, Camila F.; Almeida, Lúcia M. (Zootaxa, 2018)
Chnoodes Chevrolat, 1849 currently has 32 species described in South and Central America, with only one species, Chnoodes centralis Sicard, 1912 described from French Guiana. Here, C. centralis is redescribed and five new species are described: C. brulei sp. nov. (holotype male: Commune de Roura, Montagne des Chevaux), C. rubra sp. nov. (holotype male: Commune de Roura, Montagne des Chevaux), C. cerasus sp. nov. (holotype male: Commune de Roura, Montagne des Chevaux), C. tristis sp. nov. (holotype male: Commune de Kourou, Savane des Pères) and C. melanus sp. nov. (holotype male: Commune de Régina, Réserve Naturelle des Nouragues). These species can be distinguished by body color, presence or absence of spots on the pronotum and elytra, and by male and female genitalia. A distribution map and a key for the species in French Guiana are provided.